Web-Based Integrated Scheduling System at Universitas Multimedia Nusantara - Astri Forturia; J. Johny Natu Prihanto; P.M. Winarno (Conference Series, 2020)
The digital transformation strategy is carried out on scheduling at the Multimedia Nusantara University (UMN) campus in order to shorten work time and achieve space utilization rates in each semester considering the growth in the number of UMN students and the number of classes in each academic year. Various courses have their own requirements in preparing schedules that must be met so that learning outcomes can be realized. This transformation is carried out by changing the work that was previously done manually by creating a web-based integrated scheduling system for all parties involved. This transformation uses a Digital Maturity Model framework which has 5 dimensions including Customer, Strategy, Technology, Operations, and Culture. The current state for each dimension ranges from 3.17 to 3.73. Based on the results of the interview, it is hoped that it can reach level 4. The gap between the current state and the future state will be minimized by the system built in this transformation project.